Who Runs the World: Data - Gulsecen, Sevinc; Sharma, Sushil; Akadal, Emre (Istanbul University Press, 2020)
In ancient times, possessing a land and gold was the most important asset in the world. In the 21st century, "Data" is becoming the most important asset. As data activities continue to increase in speed, scale and variety, data Science and Data Analytics is becoming the new phenomenon of the 21st century. In fact, Data is considered to be the gold of the 21st Century and "data" is changing the face of our world. The organizations are becoming bigger and bigger and need a large amount of data to process for creating a business insight or intelligence. As more and more companies worldwide start offering products and services online, companies need to not only process information quickly but also to get insight about the needs, expectations, transactional behavior and responses of the customers. This mandates the companies to deal with "Data" effectively. Nowadays, "Data" is in various forms such as; texts, documents, online books, music, videos on number of different platforms such as; social media, transactional websites and many other internet based online forums. The "Data" explosion is creating newer exciting opportunities for companies and individuals at the same time, it is also creating concerns and challenges. This edited book presents the research work of several researchers who are working in the data science related areas.